Model Pembelajaran Berbasis Penstimulasian Multiple Intelligences Siswa - Legowo, Edy (Jurnal Kajian Bimbingan dan Konseling, 2017)
This article discusses the application of multiple intelligences theory in learning at school. The discussion begins by outlining the development of the concept of intelligence and multiple intelligences. Followed by explaining the impact of multiple intelligences theory in the field of education and learning in schools. The next section describes the implementation of multiple intelligences theory in classroom learning practices, namely how providing student learning experiences facilitated by teachers can stimulate students' multiple intelligences. Evaluation of student learning outcomes from the perspective of the application of multiple intelligences theory should be carried out using authentic assessments and portfolios which better facilitate students expressing or actualizing their learning outcomes in various ways according to the strength of their type of intelligence.